STUDI AWAL PEMBUATAN ASAM LEMAK SECARA ENZIMATIK DARI BUAH SEGAR KELAPA SAWIT - Yulianto, Mohammad Endy; Broto, RTD Wisnu; Pudjihastuti, Isti (Universitas Diponegoro, 2004)
Abstract Vegetable oil is one of plantation commodity, having advantages either as food or olechemical. One of the connecting bridges between vegetable oil and oleochemical industry is the conversion of vegetable oil to fatty acid. The supply of fatty acid in indonesia by import. Beside the promising market in global trading indonesia has the superiority in raw material supply for fatty acidÂ production. In indonesia, the most raw materials used for producing fatty acid naturally include crude palm oil (CPO), palm kertnel oil (PKO), and coconut oil (CNO). Fatty acid production by enzymatic from palmfruit can be reduce investation and operation cost. The objective of this research is finding a new way of product fatty acid by direct separation from palm fruit. Â The research is information of process condition in fatty acid production by enzymatic from palm fruit, by quality of fatty acid is used in cosmetics, plastic, tyre, PVC, stabilizer, paint and soap industries. The variables studied in this process include temperature, pH, and water consentration. Yield of fatty acid is analysed for quality and quantity. The quality analysis include water consentration, acid number, iod number and perokside number. The quantity analysis is used titration or chromatografi gas. The research shows that the enzyme lipase action increases by temperature increase, and optimum temperatureof lipase from palm fruit for hydrolysis reaction is 35o C. If used buffer pH of reaction, fatty acid production can be increase. Beside that, water consentration increases by fatty acid production increase to. Keywords : fatty acid, enzyme, palm fruit